A Microstrip Lowpass Filter Using a Stepped Impedance Hairpin Resonator for GPS Application - Resty Amanda; Asrizal; Pakhrur Razi; Khairi Budayawan (Research on Instrumentation, 2025)
The rapidly developing digital era today, particularly advancements in technology within the fields of navigation and information. One such technological advancement is the Global Positioning System (GPS). GPS is a satellite-based system that uses microwave signals to continuously provide accurate information on position, speed, direction, and time, independent of time and weather conditions. As a result, to obtain accurate information, a device known as a lowpass filter is required to reduce interference in the GPS receiver signal. The increasing sophistication of technology has driven the need for more efficient systems. Therefore, filters for GPS receiver applications are generally designed to be small and thin. One such filter with these characteristics is the microstrip filter. This filter has several advantages, including its small size, ease of fabrication, simplicity in production, and ease of integration into other electronic devices. This research aims to analyze the effect of adding stubs, the influence of the filter's physical dimensions, and to characterize the lowpass filter for GPS applications. The filter was designed using a stepped impedance hairpin resonator (SIHR). The substrate used was NPCH-220A with a dielectric constant of 2.17 and a substrate thickness of 1.6 mm. The proposed design complies with the specified filter specifications. Simulation results show a cutoff frequency of 1.79 GHz, return loss of -24 dB, insertion loss in the passband of -0.1 dB, and at the cutoff frequency of -3 dB. Meanwhile, the measurement results show a cutoff frequency of 1.66 GHz, return loss of -45 dB, insertion loss in the passband of -1.6 dB, and at the cutoff frequency of -3 dB. From the results of this study, the microstrip lowpass filter using a stepped impedance hairpin resonator can be used in GPS applications.